Resin composition and resin-coated copper foil

JP7651467B2Active Publication Date: 2025-03-26MITSUI MINING & SMELTING CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021554903
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-05
Filing Date
2020-10-27
Publication Date
2025-03-26
Estimated Expiration
2040-10-27

Smart Images

  • Figure 0007651467000001
    Figure 0007651467000001
Patent Text Reader

Abstract

Provided is a resin composition having excellent dielectric properties, high adhesiveness to low-roughness surfaces, heat resistance, and excellent water resistance. This resin composition includes (a) a polymer having a polyphenylene ether skeleton and a butadiene skeleton in one molecule and having at least one selected from the group consisting of a vinyl group, a styryl group, an allyl group, an ethynyl group, and a (meth)acryloyl group and at least one of (b) a polymer including a styrene-butadiene skeleton and (c) a polymer including a cycloolefin skeleton, and, relative to a total content of 100 weight parts of component (a), component (b), and component (c), the content of component (a) is 15-60 weight parts inclusive and the total content of component (b) and component (c) is 40-85 weight parts inclusive.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and a resin-coated copper foil. [Background technology]

[0002] Printed wiring boards are widely used in electronic devices such as portable electronic devices. In particular, in recent years, signals have become increasingly high-frequency with the increasing functionality of portable electronic devices, and printed wiring boards suitable for such high-frequency applications are in demand. In order to transmit high-frequency signals without degrading their quality, it is desirable for these high-frequency printed wiring boards to have low transmission loss. A printed wiring board is provided with copper foil processed into a wiring pattern and an insulating resin substrate, and the transmission loss is mainly composed of conductor loss due to the copper foil and dielectric loss due to the insulating resin substrate. Therefore, in resin-layered copper foils used for high-frequency applications, it is desirable to suppress dielectric loss due to the resin layer. For this purpose, the resin layer is required to have excellent dielectric properties, particularly a low dielectric tangent.

[0003] Meanwhile, various resin compositions with excellent dielectric properties have been proposed for use in printed wiring boards and the like. For example, Patent Document 1 (JP 2008-181909 A) discloses a circuit board composition containing a thermosetting resin substrate, glass fiber cloth, inorganic particle filler, metallic coagents, and a bromine flame retardant. The thermosetting resin substrate is made of (a) a mixture of a high molecular weight polybutadiene thermosetting resin and a low molecular weight polybutadiene thermosetting resin, and (b) a cycloolefin compound having two or more vinyl double bonds, and / or a polymer of acrylic acid, acrylic acid nitrile, and butadiene. Patent Document 2 (JP 2005-502192 A) relates to a method for forming a circuit member with a low dielectric constant and a low heat dissipation constant, and discloses that an adhesion-promoting elastomer layer is disposed between a copper foil and a circuit board material, and the copper foil, the adhesion-promoting elastomer layer, and the circuit board material are laminated to produce the circuit member. As examples of the elastomer, numerous elastomers and copolymers are listed, such as ethylene-propylene elastomers, ethylene-propylene-diene monomer elastomers, styrene-butadiene elastomers, and styrene-butadiene block copolymers. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2008-181909 A [Patent Document 2] JP 2005-502192 A Summary of the Invention

[0005] The present inventors have been studying resin compositions having excellent dielectric properties and the like that can be attached to a substrate such as a pre-glue as a primer layer (adhesive layer). The layer of this resin composition is provided in the form of a resin-coated copper foil, and this copper foil can be used as a copper foil for forming a circuit. It is desirable for the resin composition for the above-mentioned applications to have various properties such as excellent adhesion to low-roughness surfaces (for example, the surface of a low-roughness copper foil), heat resistance, and excellent water resistance, as well as excellent dielectric properties. In particular, in forming a circuit for high frequencies, a low-roughness copper foil is desirable from the viewpoint of reducing transmission loss, but such a copper foil tends to have low adhesion to the resin composition due to its low roughness. Therefore, the problem is how to achieve both excellent dielectric properties and high adhesion to a low-roughness copper foil while ensuring other properties.

[0006] The present inventors have now discovered that by blending a specific polymer having a polyphenylene ether skeleton and a butadiene skeleton in one molecule with a polymer containing a styrene-butadiene skeleton and / or a polymer containing a cycloolefin skeleton in a predetermined mixing ratio, it is possible to provide a resin composition exhibiting excellent dielectric properties (e.g., low dielectric tangent at 10 GHz), high adhesion to low-roughness surfaces (e.g., the surface of a low-roughness copper foil), heat resistance, and excellent water resistance (low water absorption).

[0007] It is therefore an object of the present invention to provide a resin composition that exhibits excellent dielectric properties, high adhesion to low roughness surfaces, heat resistance, and excellent water resistance.

[0008] According to one aspect of the invention, a composition comprising the following components: (a) a polymer having a polyphenylene ether skeleton and a butadiene skeleton in one molecule, and having at least one group selected from the group consisting of a vinyl group, a styryl group, an allyl group, an ethynyl group, and a (meth)acryloyl group; At least one of (b) a polymer containing a styrene-butadiene skeleton and (c) a polymer containing a cycloolefin skeleton, A resin composition comprising: The resin composition is provided in which the content of the component (a) is 15 parts by weight or more and 60 parts by weight or less, and the total content of the component (b) and the component (c) is 40 parts by weight or more and 85 parts by weight or less, relative to 100 parts by weight of the total content of the component (a), the component (b), and the component (c).

[0009] According to another aspect of the present invention, there is provided a resin-coated copper foil comprising a copper foil and a resin layer made of the resin composition provided on at least one surface of the copper foil. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] resin composition The resin composition of the present invention contains (a) a polymer (hereinafter referred to as component (a)) having a polyphenylene ether skeleton and a butadiene skeleton in one molecule, and having at least one selected from the group consisting of a vinyl group, a styryl group, an allyl group, an ethynyl group, and a (meth)acryloyl group. This resin composition further contains at least one of (b) a polymer containing a styrene-butadiene skeleton (hereinafter referred to as component (b)) and (c) a polymer containing a cycloolefin skeleton (hereinafter referred to as component (c)). The content of component (a) is 15 parts by weight or more and 60 parts by weight or less, and the total content of components (b) and (c) is 40 parts by weight or more and 85 parts by weight or less, relative to 100 parts by weight of the total content of components (a), (b), and (c). In this way, by blending a specific polymer having a polyphenylene ether skeleton and a butadiene skeleton in one molecule with a polymer containing a styrene-butadiene skeleton and / or a polymer containing a cycloolefin skeleton at a specific mixing ratio, it is possible to provide a resin composition exhibiting excellent dielectric properties (e.g., low dielectric tangent at 10 GHz), high adhesion to low-roughness surfaces (e.g., the surface of low-roughness copper foil), heat resistance, and excellent water resistance (low water absorption). In addition, this resin composition also has good processability, for example, it is not easily cracked and can exhibit good tackiness.

[0011] As mentioned above, the present inventors have been studying a resin composition having excellent dielectric properties and the like, which can be attached to a substrate such as a pre-glue as a primer layer (adhesive layer). The layer of this resin composition is provided in the form of a resin-coated copper foil, and this copper foil can be used as a copper foil for forming a circuit. It is desired that the resin composition for the above-mentioned use has various properties such as excellent adhesion to a low-roughness surface (for example, the surface of a low-roughness copper foil), heat resistance, and excellent water resistance, as well as excellent dielectric properties. In particular, in the formation of a circuit for high frequency, a low-roughness copper foil is desired from the viewpoint of reducing transmission loss, but such a copper foil tends to have low adhesion to the resin composition due to its low roughness. That is, when a material having a low-roughness surface (for example, a low-roughness copper foil) is adhered to an adherend such as a substrate using a primer layer (adhesive layer) of the resin composition (for example, in the form of a resin-coated copper foil), peeling often occurs at the interface between the low-roughness surface, which is a flatter interface, and the resin composition layer. This is believed to be because the unevenness of the interface is extremely small (the thickness of the region where the interface exists is extremely thin), and the tensile stress is two-dimensionally concentrated at the flat interface, which has the weakest adhesion strength.

[0012] If this tensile stress can be received by a layer of a resin composition (hereinafter referred to as a resin layer) in a more three-dimensional manner rather than a two-dimensional interface (i.e., if the stress can be dispersed to the inside of the resin layer), peeling at the interface may be prevented and the adhesive strength may be improved. As a measure to improve the adhesive strength, it is possible to reduce the elastic modulus of the resin layer that receives the stress, increase the elongation rate of the resin layer, increase the thickness of the resin layer, or form a different phase such as a filler inside the resin layer. However, although the method of giving flexibility to the resin layer, such as reducing the elastic modulus or increasing the elongation rate, can improve the peel strength (adhesion) of the resin-coated copper foil at room temperature, the thermal properties such as the heat resistance of the resin layer tend to be deteriorated depending on the flexible resin. In addition, when the thickness of the resin layer is increased, the thinness of the resin is sacrificed, and the thickness of the substrate when the substrate is laminated is increased. In addition, when forming a different phase such as a filler in a resin layer, it is necessary to control the phase interface, such as ensuring the adhesion of the phase interface, optimizing the specific surface area of ​​the phase interface, and ensuring the dispersibility of the phase in the manufacturing process, and the like. Unless such complex phase interface control is achieved, the effect of improving the peel strength cannot be obtained. In this respect, the resin composition of the present invention can advantageously solve the above problem. This is thought to be because the polymer component (a) is blended with the polymer component (b) and / or (c) at a predetermined compounding ratio, thereby creating a continuous polymer-polymer interface (micro-controlled phase separation structure) in the resin composition by the polymer alloy. That is, when tensile stress is applied in a peel strength test or the like in the form of a resin-coated copper foil, the resin layer is deformed before peeling occurs at the interface between the copper foil layer and the resin composition layer, and the tensile stress is dispersed throughout the thickness direction of the resin layer through the continuous interface between the polymers, and the tensile stress can be absorbed by the entire resin layer. That is, the resin composition of the present invention can form a resin layer that has not only excellent dielectric properties but also heat resistance and water resistance, and can receive tensile stress three-dimensionally, so that it is believed that high adhesion (high peel strength) to a low roughness surface can be realized. Thus, the present invention provides a resin composition that exhibits excellent dielectric properties, high adhesion to a low roughness surface, heat resistance, and excellent water resistance.

[0013] Specifically, the resin composition of the present invention preferably has a dielectric loss tangent at a frequency of 10 GHz after curing of less than 0.0030, more preferably less than 0.0020, and even more preferably less than 0.0015. The dielectric loss tangent is preferably low, and the lower limit is not particularly limited, but is typically 0.0001 or more. In addition, the resin composition of the present invention preferably has a water absorption rate measured in accordance with JIS C 6481-1996 after curing of less than 0.5%, more preferably less than 0.3%, and even more preferably less than 0.1%. The water absorption rate is preferably low, and the lower limit is not particularly limited, but is typically 0.01% or more.

[0014] The resin composition of the present invention contains component (a). Component (a) is a component that mainly contributes to thermosetting properties and heat resistance, and is a polymer having a polyphenylene ether skeleton and a butadiene skeleton in one molecule and having a predetermined reactive functional group. The predetermined reactive functional group is at least one selected from a vinyl group, a styryl group, an allyl group, an ethynyl group, and a (meth)acryloyl group, and an optimal one may be selected depending on the degree of reactivity to be imparted, but from the viewpoint of versatility, a vinyl group is preferable. In addition, the polyphenylene ether skeleton and the butadiene skeleton may be in any polymerization form, but from the viewpoint of heat resistance, it is preferable that they are polymerized via ester condensation. The proportion of the polyphenylene ether skeleton in component (a) is not particularly limited, but from the viewpoint of heat resistance, it is preferable that it is a high ratio, specifically, 30% by weight or more and 80% by weight or less, more preferably 50% by weight or more and 70% by weight or less. The vinyl group in the butadiene skeleton of component (a) can take the form of 1,2-vinyl group and 1,4-vinyl group. From the viewpoint of heat resistance and weather resistance, it is preferable that the 1,4-vinyl group is as small as possible, and in the extreme case, hydrogenation (hydrogenation treatment) may be performed. The molar ratio of 1,4-vinyl group to the total of 1,2-vinyl group and 1,4-vinyl group is preferably 30% or less, more preferably 20% or less, and further preferably 15% or less. A preferred example of component (a) is BX-660T manufactured by Nippon Kayaku Co., Ltd.

[0015] The content of component (a) is from 15 to 60 parts by weight, preferably from 20 to 55 parts by weight, more preferably from 20 to 40 parts by weight, and even more preferably from 25 to 35 parts by weight, relative to 100 parts by weight of the total content of components (a), (b), and (c). By being within these ranges, the above-mentioned properties can be more effectively achieved.

[0016] The resin composition of the present invention further contains at least one of component (b) and component (c). Component (b) is a component that mainly contributes to peel strength and dielectric properties, and is a polymer containing a styrene-butadiene skeleton (typically a block copolymer of styrene and butadiene). This polymer may be either hydrogenated or non-hydrogenated, but hydrogenation is preferred from the viewpoint of weather resistance. In terms of balancing the dielectric properties, flexibility, and peel strength, component (b) preferably has a styrene / ethylene-butylene ratio (S / EB ratio) in the range of 10 / 90 to 60 / 40, more preferably 20 / 80 to 40 / 60, and even more preferably 25 / 75 to 35 / 65. A preferred example of component (b) is Tuftec® (Tuftec®) manufactured by Asahi Kasei Corporation. (R) MP-10. On the other hand, component (c) is a component that mainly contributes to dielectric properties, heat resistance, and peeling after heating, and is a polymer containing a cycloolefin skeleton, and those generally called cycloolefin polymers (COP) can be used. A preferred example of component (c) is L-3PS manufactured by Zeon Corporation.

[0017] The total content of components (b) and (c) is 40 to 85 parts by weight, preferably 45 to 80 parts by weight, more preferably 60 to 80 parts by weight, and even more preferably 65 to 75 parts by weight, relative to 100 parts by weight of the total content of components (a), (b), and (c). By being within these ranges, the above-mentioned properties can be more effectively realized.

[0018] The resin composition of the present invention preferably contains both component (b) and component (c). In this case, the weight ratio b / c of ​​component (b) to component (c) is preferably 0.8 to 10.0, more preferably 1.0 to 8.0, even more preferably 1.2 to 6.0, and particularly preferably 1.2 to 4.5. By using components (b) and (c) in combination, and particularly by setting their weight ratio b / c within the above range, the adhesion to a low roughness surface (for example, the surface of a low roughness copper foil) can be further improved. This is because the styrene butadiene skeleton of component (b) and the cycloolefin skeleton of component (c) are completely different skeletons and generally do not mix easily, whereas in the resin composition of the present invention, a micro-controlled phase separation structure due to the polymer alloy can be more effectively created in the resin layer. That is, when tensile stress is applied in a peel strength test or the like in the form of a resin-coated copper foil, the tensile stress is more highly dispersed throughout the entire thickness direction of the resin layer through the fine and continuous interface between components (b) and (c), and the tensile stress is more effectively absorbed by the entire resin layer. In this way, a resin layer capable of receiving tensile stress three-dimensionally can be realized in a more effective manner.

[0019] The resin composition of the present invention preferably further comprises a silane coupling agent as component (d). The silane coupling agent contributes to adhesion. As the silane coupling agent, various silane coupling agents such as amino-functional silane coupling agents, acrylic-functional silane coupling agents, methacrylic-functional silane coupling agents, epoxy-functional silane coupling agents, olefin-functional silane coupling agents, mercapto-functional silane coupling agents, and vinyl-functional silane coupling agents can be used. In particular, a silane coupling agent consisting of a silane compound having a total of three methoxy groups and / or ethoxy groups in the molecule is preferred, and specific examples of such silane coupling agents include 8-methacryloxyoctyltrimethoxysilane, 8-glycidoxyoctyltrimethoxysilane, N-2-(aminoethyl)-8-aminooctyltrimethoxysilane, p-styryltrimethoxysilane, 7-octenyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, and the like. The content of component (d), i.e., the silane coupling agent, is preferably 0.10 parts by weight or more and 10.0 parts by weight or less, relative to 100 parts by weight of the total content of components (a), (b), and (c). From the viewpoint of suppressing adverse effects on dielectric properties, etc. due to the addition of the coupling agent, the content is more preferably 0.10 parts by weight or more and 5.0 parts by weight or less, even more preferably 0.10 parts by weight or more and 3.0 parts by weight or less, particularly preferably 0.10 parts by weight or more and 2.0 parts by weight or less, and most preferably 0.1 parts by weight or more and 1.5 parts by weight or less.

[0020] The resin composition of the present invention may further contain an inorganic filler as component (e). Examples of inorganic fillers include silica, talc, boron nitride (BN), and the like. The inorganic filler is not particularly limited as long as it can be dispersed in the resin composition, but silica is preferred from the viewpoint of dispersibility and dielectric properties. The average particle diameter D50 of the inorganic filler is preferably 0.1 to 3.0 μm, more preferably 0.3 to 2.0 μm. When the average particle diameter D50 is within such a range, the interface (i.e., the specific surface area) is reduced, thereby reducing adverse effects on the dielectric properties, and various properties preferable for electronic materials are obtained, such as improved interlayer insulation and no coarse particles in the resin layer. The inorganic filler may be in any form, such as crushed particles, spherical particles, core-shell particles, hollow particles, and the like. The content of component (e), i.e., the inorganic filler, is preferably 50 parts by weight or more and 400 parts by weight or less, more preferably 50 parts by weight or more and 250 parts by weight or less, even more preferably 50 parts by weight or more and 200 parts by weight or less, and particularly preferably 50 parts by weight or more and 150 parts by weight or less, relative to 100 parts by weight of the total content of components (a), (b), and (c).

[0021] Resin Coated Copper Foil The resin composition of the present invention is preferably used as a resin for a resin-coated copper foil. That is, according to a preferred embodiment of the present invention, a resin-coated copper foil is provided, which includes a copper foil and a resin layer made of a resin composition provided on at least one surface of the copper foil. Typically, the resin composition is in the form of a resin layer, and the resin composition is applied to the copper foil using a gravure coating method so that the thickness of the resin layer after drying is a predetermined value, and then dried to obtain a resin-coated copper foil. The coating method is arbitrary, and in addition to the gravure coating method, a die coating method, a knife coating method, etc. can be adopted. In addition, it is also possible to coat using a doctor blade, a bar coater, etc.

[0022] As described above, the resin composition of the present invention exhibits excellent dielectric properties (e.g., low dielectric tangent at 10 GHz), high adhesion to low-roughness surfaces (e.g., surfaces of low-roughness copper foils), heat resistance, and excellent water resistance (low water absorption). Therefore, the resin-coated copper foil has various advantages brought about by such a resin composition. For example, the lower limit of the peel strength (i.e., normal peel strength) between the resin layer and the copper foil, measured in accordance with JIS C 6481-1996 in a cured state of the resin layer, is preferably 0.6 kgf / cm or more, more preferably 0.7 kgf / cm or more, and particularly preferably 0.8 kgf / cm or more. The higher the peel strength, the better, and the upper limit is not particularly limited, but is typically 2.0 kgf / cm or less.

[0023] The resin-coated copper foil can also exhibit high peel strength even after heating. Specifically, the lower limit of the peel strength between the resin layer and the copper foil (i.e., peel strength after heating) measured according to JIS C 6481-1996 after the resin layer is cured and heated at 260°C for 60 minutes is preferably 0.5 kgf / cm or more, more preferably 0.6 kgf / cm or more, even more preferably 0.7 kgf / cm or more, and particularly preferably 0.8 kgf / cm or more. The higher the peel strength after heating, the better, and the upper limit is not particularly limited, but is typically 2.0 kgf / cm or less.

[0024] The thickness of the resin layer is not particularly limited, but since a thicker resin layer is preferable to ensure peel strength, and a thinner laminate substrate is preferable, there is an appropriate thickness. The thickness of the resin layer is preferably 1 μm or more and 50 μm or less, more preferably 2 μm or more and 20 μm or less, particularly preferably 3 μm or more and 10 μm or less, and most preferably 3 μm or more and 5 μm or less. By being within these ranges, the above-mentioned characteristics of the present invention can be more effectively realized, and the resin layer can be easily formed by applying the resin composition.

[0025] The copper foil may be a metal foil (so-called raw foil) that has been electrolytically or rolled, or may be in the form of a surface-treated foil that has been surface-treated on at least one side. The surface treatment may be any of various surface treatments that are performed to improve or impart certain properties (e.g., rust resistance, moisture resistance, chemical resistance, acid resistance, heat resistance, and adhesion to a substrate) to the surface of the metal foil. The surface treatment may be performed on one side of the metal foil or on both sides of the metal foil. Examples of surface treatments performed on copper foil include rust prevention treatment, silane treatment, roughening treatment, and barrier formation treatment.

[0026] The ten-point average roughness Rzjis of the surface of the resin layer side of the copper foil measured according to JIS B0601-2001 is preferably 0.5 μm or less, more preferably 0.4 μm or less, even more preferably 0.3 μm or less, and particularly preferably 0.2 μm or less. Within such a range, the transmission loss in high frequency applications can be desirably reduced. That is, the conductor loss caused by the copper foil, which may increase due to the skin effect of the copper foil that becomes more noticeable at higher frequencies, can be reduced, thereby achieving further reduction in transmission loss. The lower limit of the ten-point average roughness Rzjis of the surface of the resin layer side of the copper foil is not particularly limited, but from the viewpoint of improving adhesion with the resin layer and heat resistance, Rzjis is preferably 0.01 μm or more, more preferably 0.03 μm or more, and even more preferably 0.05 μm or more.

[0027] The thickness of the copper foil is not particularly limited, but is preferably 0.1 μm or more and 100 μm or less, more preferably 0.5 μm or more and 70 μm or less, even more preferably 1 μm or more and 50 μm or less, particularly preferably 1.5 μm or more and 30 μm or less, and most preferably 2 μm or more and 20 μm or less. If the thickness is within these ranges, it is advantageous in that fine circuits can be formed. However, when the thickness of the copper foil is, for example, 10 μm or less, the resin-coated copper foil of the present invention may be a carrier-coated copper foil having a release layer and a carrier, and a resin layer formed on the copper foil surface of the carrier-coated copper foil to improve handling. EXAMPLES

[0028] The present invention will now be further illustrated by the following examples.

[0029] Examples 1-11 (1) Preparation of resin varnish First, the following components (a) to (e) were prepared as raw materials for a resin varnish. - Component (a): A thermosetting polymer having a polyphenylene ether skeleton and a butadiene skeleton in one molecule and having a vinyl group as a reactive functional group (manufactured by Nippon Kayaku Co., Ltd., BX-660T) - Component (b): Hydrogenated styrene butadiene polymer (thermoplastic polymer) (manufactured by Asahi Kasei Corporation, Tuftec (R) , Part number: MP-10, Styrene / Ethylene-Butylene ratio (S / EB ratio) = 30 / 70) - Component (c): Cycloolefin polymer (thermoplastic polymer) (manufactured by Zeon Corporation, L-3PS) - Component (d): Silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., KBM-1403, p-styryltrimethoxysilane) - Component (e): Silica particles (manufactured by Admatechs Co., Ltd., Adma Fine, product number: SC4050-MOT, average particle size D50: 1.0 μm)

[0030] The raw materials were weighed into a round flask in the blending ratio (weight ratio) shown in Table 1, and a mixed solvent was added so that the raw material concentration was 28% by weight or 40% by weight. This mixed solvent was configured so that the ratio of the organic solvent in the resin varnish was 85% by weight of toluene and 15% by weight of methyl ethyl ketone. A mantle heater, a stirring blade, and a flask lid with a reflux condenser were placed in the round flask containing the raw materials and the mixed solvent, and the temperature was raised to 60°C while stirring, and then stirring was continued at 60°C for 2 hours to dissolve or disperse the raw materials. The mixed solution obtained after stirring was allowed to cool. In this way, a resin varnish with a raw material concentration of 28% by weight and a resin varnish with a raw material concentration of 40% by weight were obtained, respectively.

[0031] (2) Preparation of electrolytic copper foil An electrolytic copper foil (thickness 18 μm) was prepared by the following method. In a copper sulfate solution, a rotating titanium electrode (surface roughness Ra: 0.20 μm) was used as the cathode and a dimensionally stable anode (DSA) was used as the anode, and the solution temperature was 45°C and the current density was 55 A / dm 2 The electrolysis was performed at 1000 K to produce electrolytic copper foil as the original foil. The composition of this copper sulfate solution was copper concentration 80 g / L, free sulfuric acid concentration 140 g / L, bis(3-sulfopropyl) disulfide concentration 30 mg / L, diallyldimethylammonium chloride polymer concentration 50 mg / L, and chlorine concentration 40 mg / L. Particulate protrusions were formed on the surface of the original foil facing the electrolyte. The particulate protrusions were formed in a copper sulfate solution (copper concentration: 13 g / L, free sulfuric acid concentration 55 g / L, 9-phenylacridine concentration 140 mg / L, chlorine concentration: 35 mg / L) at a solution temperature of 30°C and a current density of 50 A / dm 2 The electrolysis was carried out under the following conditions.

[0032] On the electrolyte side of the thus obtained original foil, a zinc-nickel coating film, a chromate layer, and a silane layer were successively formed under the conditions shown below. <Zinc-nickel coating formation> Potassium pyrophosphate concentration: 80g / L Zinc concentration: 0.2g / L Nickel concentration: 2g / L Liquid temperature: 40℃ ·Current density: 0.5A / dm 2 <Chromate layer formation> Chromic acid concentration: 1g / L, pH 11 ·Solution temperature: 25℃ ·Current density: 1A / dm 2 <Silane layer formation> Silane coupling agent: 3-aminopropyltrimethoxysilane (3g / L aqueous solution) Liquid treatment method: Shower treatment

[0033] The surface treatment surface of this electrolytic copper foil has a ten-point average roughness Rzjis of 0.5 μm (based on JIS B0601-2001), and the particulate protrusions have an average particle diameter of 100 nm and a particle density of 205 particles / μm 2 It was.

[0034] (3) Preparation of resin film The obtained resin varnish having a raw material component concentration of 40% by weight was applied to the surface of the electrolytic copper foil using a comma coater so that the thickness of the resin after drying would be 50 μm, and then dried in an oven at 150 ° C for 3 minutes to obtain a resin-coated copper foil. Two sheets of the obtained resin-coated copper foil were laminated together so that the resins were in contact with each other, and then dried at 190 ° C for 90 minutes with 20 kgf / cm 2 A double-sided copper-clad laminate was produced by vacuum press molding under the conditions of 1. The copper on both sides of the obtained double-sided copper-clad laminate was entirely removed by etching to obtain a resin film having a thickness of 100 μm.

[0035] (4) Preparation of thick films The obtained resin varnish with a raw material concentration of 40% by weight was applied to a release film (AGC's "Aflex (R) The release film was peeled off from the obtained B-stage resin, and 20 sheets of the B-stage resin were laminated together. The laminate was then heated at 190°C for 90 minutes under 20 kgf / cm. 2 A thick film having a thickness of 1000 μm was obtained by vacuum press molding under the above conditions.

[0036] (5) Fabrication of single-surface layer substrate The obtained resin varnish having a raw material component concentration of 28% by weight was applied to the surface of the electrolytic copper foil using a gravure coater so that the resin would have a thickness of 4 μm after drying, and then dried in an oven at 150° C. for 2 minutes to obtain a resin-coated copper foil. A number of prepregs (Panasonic "R-5680") were layered to a thickness of 0.2 mm, and the resin-coated copper foil was laminated thereon so that the resin was in contact with the prepreg, and the resulting laminate was dried at 190° C. for 90 minutes under 30 kgf / cm 2A single area layer substrate was obtained by vacuum press molding under the above conditions.

[0037] (6) Preparation of double-sided laminated board The obtained resin varnish having a raw material component concentration of 28% by weight was applied to the surface of the electrolytic copper foil using a gravure coater so that the resin would be 4 μm thick after drying, and then dried in an oven at 150° C. for 2 minutes to obtain a resin-coated copper foil. A prepreg (Panasonic "R-5680") was layered to a thickness of 0.2 mm, and the resin-coated copper foil was laminated on both the top and bottom sides of the prepreg so that the resin was in contact with the prepreg, and then the laminate was dried at 190° C. for 90 minutes under 30 kgf / cm 2 A double-sided laminated substrate was obtained by vacuum press molding under the above conditions.

[0038] (7) Various evaluations The prepared resin film, thick film, single-area laminate substrate and double-sided laminate substrate were evaluated as follows.

[0039] <Evaluation 1: Normal peel strength> A copper wiring with a wiring width of 10 mm and a wiring thickness of 18 μm was formed on a single-sided laminate board by a subtractive method, and the peel strength was measured at room temperature (e.g., 25° C.) in accordance with JIS C 6481-1996. The measurement was performed five times, and the average value was taken as the normal peel strength value and evaluated according to the following criteria. The peel strength measured here is a value that reflects four peel modes: interfacial peeling between prepreg and resin, cohesive failure of the resin, interphase interfacial peeling within the resin layer, and interfacial peeling between resin and copper foil, and the higher the value, the better the adhesion to the prepreg base material, the strength of the resin layer, and the adhesion of the resin to the low-roughness foil. The results were as shown in Table 1. - Rating A: 0.8kgf / cm or more - Rating B: 0.7kgf / cm or more and less than 0.8kgf / cm - Rating C: 0.6kgf / cm or more and less than 0.7kgf / cm - Rating D: Less than 0.6kgf / cm

[0040] <Evaluation 2: Peel strength after heating> A copper wiring with a wiring width of 10 mm and a wiring thickness of 18 μm was formed on a single-surface laminate board by a subtractive method, and after heat treatment in an oven at 260°C for 60 minutes, the peel strength was measured in accordance with JIS C 6481-1996. Note that the peel strength was not measured at 260°C, but after cooling from there to room temperature (e.g., 25°C) (JIS C 6481-1996 states that the measurement should be performed at a standard temperature of 15 to 35°C). The measurement was performed five times, and the average value was taken as the value of the peel strength after heating, and was evaluated according to the following criteria. The results are shown in Table 1. - Rating A: 0.7kgf / cm or more - Rating B: 0.6kgf / cm or more and less than 0.7kgf / cm - Rating C: 0.5kgf / cm or more and less than 0.6kgf / cm - Rating D: Less than 0.5kgf / cm

[0041] <Evaluation 3: Heat resistance> The double-sided laminated substrate was cut into a size of 0.7 cm square, and the T-288 heat resistance was evaluated in accordance with IPC-TM-650 using a thermomechanical analyzer (TMA) (Hitachi High-Technologies Corporation, TMA7100). This evaluation was performed by increasing the temperature from room temperature to 288°C at a rate of 10°C / min in a nitrogen atmosphere, holding at 288°C for 120 minutes, applying a compressive load of 10 mN during that time, and monitoring the displacement of the probe. In other words, if gas generation such as thermal decomposition occurs, the double-sided laminated substrate will swell and be detected as a displacement. The maximum displacement measured in this way during the 120 minutes was applied to the following criteria to rank and evaluate the heat resistance. The results are shown in Table 1. - Rating A: Maximum displacement of less than 50 μm during 120 minutes (no or small swelling) - Rating D: Maximum displacement over 50 μm in 120 minutes (large swelling)

[0042] <Evaluation 4: Dielectric tangent> The dielectric loss tangent at 10 GHz of the resin film alone was measured by the perturbation cavity resonator method. This measurement was performed in accordance with JIS R 1641 using a measuring device (a KEYCOM resonator and a KEYSIGHT network analyzer) after cutting the resin film alone to fit the sample size of the resonator. The measured dielectric loss tangent was rated and evaluated according to the following criteria. The results are shown in Table 1. - Rating A: Dielectric tangent at 10 GHz is less than 0.0015 - Rating B: Dielectric tangent at 10 GHz is 0.0015 or more and less than 0.0020 - Rating C: Dielectric tangent at 10 GHz is 0.0020 or more and less than 0.0030 - Rating D: Dielectric tangent at 10 GHz is 0.0030 or more

[0043] <Evaluation 5: Water absorption rate> Five test pieces measuring 50 mm x 50 mm were cut out from the thick film. The water absorption of these test pieces was measured in accordance with JIS C 6481-1996, and the average value was taken as the representative value of the water absorption and evaluated according to the following criteria. The results are shown in Table 1. - Rating A: Water absorption rate is less than 0.1% - Rating B: Water absorption rate is 0.1% or more but less than 0.3% - Rating C: Water absorption rate is 0.3% or more but less than 0.5% - Rating D: Water absorption rate is 0.5% or more

[0044] [Table 1]

Claims

1. The following ingredients: (a) a polymer having a polyphenylene ether skeleton and a polybutadiene skeleton in one molecule and having at least one reactive functional group selected from the group consisting of a vinyl group, a styryl group, an allyl group, an ethynyl group, and a (meth)acryloyl group; (b) at least one of a polymer containing a styrene-butadiene skeleton and (c) a polymer containing a cycloolefin skeleton; A resin composition comprising: A resin composition, wherein the content of the component (a) is 15 parts by weight or more and 55 parts by weight or less, and the total content of the component (b) and the component (c) is 40 parts by weight or more and 85 parts by weight or less, relative to 100 parts by weight of the total content of the components (a), (b), and (c).

2. The resin composition according to claim 1, wherein the content of the component (a) is 20 parts by weight or more and 55 parts by weight or less.

3. The resin composition according to claim 1 or 2, comprising both the component (b) and the component (c).

4. The resin composition according to claim 3, wherein a weight ratio b / c of ​​the component (b) to the component (c) is 0.8 or more and 10.0 or less.

5. The resin composition further comprises (d) a silane coupling agent, The content of the component (d) is 0.10 parts by weight or more and 10.0 parts by weight or less relative to 100 parts by weight of the total content of the components (a), (b), and (c). The resin composition according to any one of claims 1 to 4.

6. The resin composition further comprises (e) an inorganic filler, The content of the component (e) is 50 parts by weight or more and 400 parts by weight or less relative to 100 parts by weight of the total content of the components (a), (b) and (c). The resin composition according to any one of claims 1 to 5.

7. The resin composition according to any one of claims 1 to 6, having a dielectric loss tangent at a frequency of 10 GHz after curing of less than 0.0030.

8. The resin composition according to any one of claims 1 to 7, which has a water absorption rate after curing of less than 0.5% as measured in accordance with JIS C 6481-1996.

9. A resin-coated copper foil comprising a copper foil and a resin layer formed on at least one surface of the copper foil, the resin layer being made of the resin composition according to any one of claims 1 to 8.

10. The resin-coated copper foil according to claim 9, wherein the ten-point average roughness Rzjis of the surface of the copper foil on the resin layer side, measured in accordance with JIS B0601-2001, is 0.5 μm or less.

11. The resin-coated copper foil according to claim 9 or 10, wherein the normal peel strength between the resin layer and the copper foil, measured in accordance with JIS C 6481-1996, is 0.6 kgf / cm or more when the resin layer is cured.

12. The resin-coated copper foil according to any one of claims 9 to 11, wherein the peel strength between the resin layer and the copper foil, measured in accordance with JIS C 6481-1996 after the resin layer is cured and heated at 260 ° C. for 60 minutes, is 0.5 kgf / cm or more.

Citation Information

Patent Citations

  • Nannenjushisoseibutsu

    JP1976067354A

  • Production of polyphenylene ether resin composition

    JP1983098359A

  • Polyphenylene ether composition

    JP1985053554A

  • Method for improving the adhesion of circuit boards to metals and articles made therefrom

    JP2005502192A

  • Phosphorus-containing mixture, method of producing the same and its use

    JP2007254741A